Comparison of Hardy-Littlewood and dyadic maximal functions on spaces of homogeneous type - Aimar, Hugo Alejandro (2005)
We obtain a comparison of the level sets for two maximal functions on a space of homogeneous type: the Hardy-Littlewood maximal function of mean values over balls and the dyadic maximal function of mean values over the dyadic sets introduced by M. Christ in [M. Christ, A T (b) theorem with remarks on analytic capacity and the Cauchy integral, Colloq. Math. 60/61 (1990) 601-628]. As applications to the theory of Ap weights on this setting, we compare the standard and the dyadic Muckenhoupt classes and we give an alternative proof of reverse Hölder type inequalities.